2021
DOI: 10.12965/jer.2142322.161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vibration foam rolling on the range of motion in healthy adults: a systematic review and meta-analysis

Abstract: Professionals use foam rollers to improve range of motion (ROM). Recently, a vibrating foam roller (VFR) that combines the vibration function with a foam roller (FR) has been used. The purpose of this systematic review and meta-analysis was to determine the effects of a VFR on the improvement of ROM in healthy individuals. A systematic literature search was carried out in five international databases: PubMed, Embase, PEDro, Cochrane Library, and Google Scholar. Eight clinical studies, composed of six randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Numerous articles have investigated the acute effects of foam rolling on flexibility and force output as well as passive properties, using different degrees of roller hardness, 9 rolling velocities, 10 roller massagers, 11 and combinations of foam rolling with or without stretching and/or vibration. 12 , 13 , 14 They found meaningful ROM increases, which are considered comparable to those of stretching. 15 , 16 …”
Section: Introductionmentioning
confidence: 81%
“…Numerous articles have investigated the acute effects of foam rolling on flexibility and force output as well as passive properties, using different degrees of roller hardness, 9 rolling velocities, 10 roller massagers, 11 and combinations of foam rolling with or without stretching and/or vibration. 12 , 13 , 14 They found meaningful ROM increases, which are considered comparable to those of stretching. 15 , 16 …”
Section: Introductionmentioning
confidence: 81%
“…This review had the practical objective of summarizing the evidence on the effect of FR in individuals with chronic and acute musculoskeletal pain. Given the reviews previously carried out on the use of FR for indirect markers of muscle damage in healthy individuals 24 , movement, muscle recovery, and performance 3, 12, 13, 25-31 , range of motion for ankle dorsi exion in healthy adults 32 , Motion, muscle recovery, performance associated with exercise programs focused on stretching 33,34 and use of vibrational FR on the range of motion and performance of normal individuals 35,36 . This is the rst systematic review that summarizes the results of studies using vibrational or non-vibrational FR on the outcome variable pain intensity in individuals with chronic and acute musculoskeletal pain.…”
Section: Discussionmentioning
confidence: 99%
“…This is echoed by Nakamura et al (99) who found that when combined with static stretching, foam rolling (both conventional and vibrating) increased knee ROM with no clear advantage provided by vibration other than the heightened mechanoreceptor response, which is suggested to provide protective benefits against stretch-induced force decrements (10,99). Nonetheless, a systematic review with meta-analysis (101) found that a vibrating foam roller induced greater improvements in ROM when compared with a nonvibrating foam roller, especially at the hip and knee joints for healthy individuals and athletes, supported by further evidence that chronic application of vibration during stretching improves ROM (82).…”
Section: Effective Self-massage Toolsmentioning
confidence: 99%